Hematologic presentation and the role of untargeted metabolomics analysis in monitoring treatment for riboflavin transporter deficiency. Issue 11 (10th September 2020) - Pillai, Nishitha R.; Amin, Hitha; Gijavanekar, Charul; Liu, Ning; Issaq, Niveen; Broniowska, Katarzyna A.; Bertuch, Alison A.; Sutton, V. Reid; Elsea, Sarah H.; Scaglia, Fernando
Abstract: Riboflavin transporter deficiency (RTD) (MIM #614707) is a neurogenetic disorder with its most common manifestations including sensorineural hearing loss, peripheral neuropathy, respiratory insufficiency, and bulbar palsy. Here, we present a 2‐year‐old boy whose initial presentation was severe macrocytic anemia necessitating multiple blood transfusions and intermittent neutropenia; he subsequently developed ataxia and dysarthria. Trio‐exome sequencing detected compound heterozygous variants in SLC52A2 that were classified as pathogenic and a variant of uncertain significance. Bone marrow evaluation demonstrated megaloblastic changes. Notably, his anemia and neutropenia resolved after treatment with oral riboflavin, thus expanding the clinical phenotype of this disorder. We reiterate the importance of starting riboflavin supplementation in a young child who presents with macrocytic anemia and neurological features while awaiting biochemical and genetic work up. We detected multiple biochemical abnormalities with the help of untargeted metabolomics analysis associated with abnormal flavin adenine nucleotide function which normalized after treatment, emphasizing the reversible pathomechanisms involved in this disorder. The utility of untargeted metabolomics analysis to monitor the effects of riboflavin supplementation in RTD has not been previously reported.